Molecular Weight and Thermal Properties of Biopolymer - Monika V. Jagtap, Rashmi M. Kenvat, Balaji S.Selukar, Gayatri S. Kamble (Mathematical Statistician and Engineering Applications, 2021)
In his paper the degradation study of polylactic acid in soil at room temperature was studied to know the effect of microorganism present in domestic compost. Reduction in molecular weight studied by by Gel Permeation Chromatrography (GPC) from 75000 to 22400. Differential Scanning Calorimetry (DSC) was investigated. Through the investigation by DSC showed changes in melting temperature from 171 degree centigrade to 162 degree centigrade which confirmed decrease in crystalline nature and degradation of polylactic acid. Scanning Electron Microscopy (SEM) results showed that formation of small pores on the surface of Polylactic acid (PLA) which supports GPC, DSC data for degradation of PLA.